2017
DOI: 10.1021/acsami.7b07525
|View full text |Cite
|
Sign up to set email alerts
|

Room-Temperature Fabrication of High-Performance Amorphous In–Ga–Zn–O/Al2O3 Thin-Film Transistors on Ultrasmooth and Clear Nanopaper

Abstract: Integrating biodegradable cellulose nanopaper into oxide thin-film transistors (TFTs) for next generation flexible and green flat panel displays has attracted great interest because it offers a viable solution to address the rapid increase of electronic waste that poses a growing ecological problem. However, a compromise between device performance and thermal annealing remains an obstacle for achieving high-performance nanopaper TFTs. In this study, a high-performance bottom-gate IGZO/AlO TFT with a dual-layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 53 publications
0
25
0
Order By: Relevance
“…Table 1 compares the performance of our RT Al 2 O 3 TFT with other reports. It is found that our device exhibits a zero-near V T , smaller SS, and larger I on/off in the case of comparable mobility [4, 23]. Although using a Ta 2 O 5 gate insulator can obtain higher mobility of 61.5 cm 2 V − 1 s − 1 , both SS and I on/off deteriorate remarkably [10].…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 compares the performance of our RT Al 2 O 3 TFT with other reports. It is found that our device exhibits a zero-near V T , smaller SS, and larger I on/off in the case of comparable mobility [4, 23]. Although using a Ta 2 O 5 gate insulator can obtain higher mobility of 61.5 cm 2 V − 1 s − 1 , both SS and I on/off deteriorate remarkably [10].…”
Section: Resultsmentioning
confidence: 99%
“…These properties are among the highest values for exible phototransistors as compared with previous reports. 18,[25][26][27] Under the same light illumination, the phototransistors exhibit almost the same transfer curves in both at and bent congurations. Fig.…”
Section: Resultsmentioning
confidence: 90%
“…However, as the demand for flexible, lightweight, transparent electronic devices keeps growing, fabricating transistors on flexible and soft substrates has increasingly attracted researchers. For flexible electronic applications, paper has been extensively explored either as a substrate, or as a transistor component (e.g., a gate dielectric of field‐effect transistors, a tunnel layer for memory transistors, etc. ), or as a dual‐purpose layer (e.g., simultaneously act as both a substrate and a gate dielectric of field‐effect transistors) .…”
Section: Electronic Circuitsmentioning
confidence: 99%
“…The recently introduced oxide TFT on nanopaper has demonstrated appealing electrical properties . In general, these type of transistors require thermal annealing processes.…”
Section: Electronic Circuitsmentioning
confidence: 99%